2011
DOI: 10.5201/ipol.2011.bcm_nlm
|View full text |Cite
|
Sign up to set email alerts
|

Non-Local Means Denoising

Abstract: We present in this paper a new denoising method called non-local means. The method is based on a simple principle: replacing the color of a pixel with an average of the colors of similar pixels. But the most similar pixels to a given pixel have no reason to be close at all. It is therefore licit to scan a vast portion of the image in search of all the pixels that really resemble the pixel one wants to denoise. The paper presents two implementations of the method and displays some results. Source CodeThe source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
476
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 817 publications
(480 citation statements)
references
References 2 publications
2
476
0
2
Order By: Relevance
“…We write here the denominator of the fraction in the exponential as h 2 , thus following the notation in [3,1,4], whereas one reads 2h 2 in most subsequent articles about NLM. The estimation of the oracle |u(x) − u(y)| is performed using the Gaussian Euclidean norm V (x) − V (y) 2,a , where a is the standard deviation of the Gaussian and where V (x) is the patch of size d × d centered at x in image v:…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We write here the denominator of the fraction in the exponential as h 2 , thus following the notation in [3,1,4], whereas one reads 2h 2 in most subsequent articles about NLM. The estimation of the oracle |u(x) − u(y)| is performed using the Gaussian Euclidean norm V (x) − V (y) 2,a , where a is the standard deviation of the Gaussian and where V (x) is the patch of size d × d centered at x in image v:…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this code does not implement any algorithmic trick or parallelization of computing, making it a slow running program. While the IPOL article [4] describes both the pixelwise NLM (NLM-P) ([1] Section 5.1) and the blockwise NLM (NLM-B) ([1] Section 5.5.2), the published demo and code implement the blockwise version only 2 . The present article aims to propose a fast and parameter-free implementation of the pixelwise NLM as described in [1] (pages 510-512).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain the best possible estimate from noisy data, a robust, efficient and reliable denoising method is required. Various denoising methods have been proposed in the last few decades, a review of which can be found in [2], where their features are elaborated and compared.…”
Section: Introductionmentioning
confidence: 99%